Pengaruh Metode Project Based Learning dalam Meningkatkan Penguasaan Kosakata Bahasa Arab pada Siswa - Baidhowi, Ahmad; Saadah, Lailatus (Lembaga Yasin AlSys, 2024)
Project based learning method learning is based on creating and creating and learning the material to be studied, while mastery of student vocabulary is carried out to improve students' abilities in Arabic vocabulary. In its implementation, researchers have tested it on January 5, 2024 at Madrasah Ibtidaiyah Miftahussa'adah in Tangerang city. This study aims to determine how much influence the project-based learning method if applied to Arabic language learning that can improve students' mastery of Arabic vocabulary in grade 5 at Madrasah Ibtidaiyah Miftahussa'adah Tangerang city by testing in the control class and experimental class. This study used a quasi-experimental method with a population of 80 students, while the sempel taken was grade 5 with a total of 18 students. Data collection techniques used in the form of interviews, documentation and tests with 10 essay questions. The results of the study were found to obtain a value of 4,325 < 5,005, so that the data obtained could be significant that Ha was accepted while Ho was rejected, with the conclusion that this research could improve students' mastery of Arabic vocabulary by applying the project-based learning method in grade 5 at Madrasah Ibtidaiyah Miftahussaadah Tangerang city.